Fecal Microbiota Transplantation Alters the Outcome of Hepatitis B Virus Infection in Mice - Wang, Junzhong; Zhou, Xin; Li, Xiaoran; Guo, Weina; Zhu, Qingfeng; Zhu, Bin; Lu, Yinping; Zheng, Xin; Yang, Dongliang; Wang, Baoju (Frontiers in Cellular and Infection Microbiology, 2022)
The susceptibility of mice to hepatitis B virus (HBV) infection depends on their genetic background. The gut microbiota modulates the antiviral immune response in the liver and plays a protective role against HBV infection. However, whether HBV infection outcomes depend on the gut microbiota remains unclear. In this study, we assessed the gut microbiota composition in naïve BALB/c and C57BL/6 mice using 16S rRNA gene sequencing. The gut microbiota in BALB/c mice was depleted using broad-spectrum antibiotics (ABX) and then reconstituted with fecal microbiota from naïve BALB/c or C57BL/6 mice to evaluate the effect of fecal microbiota transplantation (FMT) on the outcomes of and immune response to HBV infection. We found that HBV infection outcomes and the gut microbiota composition differed between BALB/c and C57BL/6 mice. Commensal bacteria from the fecal microbiota selectively colonized the guts of ABX-treated BALB/c mice. Mice receiving fecal microbiota from BALB/c or C57BL/6 mice displayed different HBV infection outcomes. The fecal microbiota from C57BL/6 mice induced immune tolerance in the liver and prolonged HBV infection. In conclusion, HBV infection outcomes in mice are determined by the host genetic background and gut microbiota composition. Reconstitution of the gut microbiota by FMT can alter the susceptibility to HBV infection in mice.